ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN SEKTOR PERTANIAN - Ridwan Idham (Panorama Nusantara, 2016)
The purpose of this research is to analyze factors that affect capital structure of agricultural sector companies in Indonesia. Capital structure is a decision that related to how company can manage the composition of financing. This research used panel model regression as method of analysis. The research revealed that tax, tangibility of assets, size, profitability, growth, percentage of credit and crisis are affect to companies capital structure. While Tax, Profitability, Percentage of credit and crisis has negative significance related with capital structure, and Tangibility of Assets has positive significance related with capital structure. There are 7 agriculture companies were selected purposively as the sample of this research, using panel data of financial report from 2011-2015. The analysis using the formula in attaining the capital structure. It is found that the revealed tax, tangibility of assets, size, profitability, growth, percentage of credit and crisis have affected companies capital structure. While Tax, Profitability, Percentage of credit and crisis have negative significance related with capital structure. The Tangibility of Assets has positive significance related with capital structure.